In vitro microbial dynamics of a Sorghum saccharatum silage enriched with and without Lactobacilli sp inoculants - Villalba, Diana Katherine (2025)
The dry matter (DM) degradation kinetics and microbial dynamics of Sorghum saccharatum (SS) enriched with additives based on Lactobacillus plantarum and Lactobacillus buchneri were determined in vitro. Three treatments were evaluated: T1: SS silage without inoculation; T2: SS silage inoculated with Lactobacillus buchneri (concentration of 6x105 CFU/g); T3: SS silage inoculated with Lactobacillus plantarum (concentration of 1x105 CFU/g), with 5 replicates each. Microbiological quality was evaluated at two fermentation times: the first day and at 21 days. Gas production was measured at 2, 4, 6, 8, 10, 12, 15, 19, 24, 30, 36, 48, and 72 hours. Likewise, DM degradation kinetics were monitored at 6, 12, 24, 48, and 72 hours. The parameters of the fermentation kinetics and degradation curves were adjusted to the models proposed by Ørskov and McDonald, using the PROC NLIN procedure of SAS. To determine the effect of treatments on DM degradation, a repeated measures analysis over time was performed using the PROC MIXED procedure of SAS. The results showed 92.9 ± 0.6 mg CO2/g dry substrate at the peak of the curve, which indicated a 37.85% decrease in the microbial population, following a logarithmic inverse trend. It is concluded that sweet sorghum has epiphytic bacteria that allow adequate fermentation performance and a good capacity to acidify the medium. Commercial additives did not affect the degradation and fermentation kinetics of the silage.